A Morphism Double Category and Monoidal Structure. (25th March 2013) - Chatterjee, Saikat; Lahiri, Amitabha; Sengupta, Ambar N.
Abstract : We provide a recipe for "fattening" a category that leads to the construction of a double category. Motivated by an example where the underlying category has vector spaces as objects, we show how a monoidal category leads to a law of composition, satisfying certain coherence properties, on the object set of the fattened category.